The effect of photodamage on the female Caucasian facial stratum corneum corneome using mass spectrometry‐based proteomics. (26th October 2017) - Voegeli, R.; Monneuse, J.‐M.; Schoop, R.; Summers, B.; Rawlings, A.V.
Abstract: Background: The effect of photodamage on facial stratum corneum (SC) is still poorly understood. Objective: To describe the SC proteome from tape strippings of Caucasian SC from photoexposed cheek and photoprotected post‐auricular (PA) site, a global analysis of photodamage on the skin will be developed leading to a better understanding of keratinocyte signalling pathways and identification of new molecular targets for the treatment of photoaged skin. Methods: Female Caucasian subjects had nine consecutive tape strippings taken from their cheeks and PA site. Proteins were extracted and the trypsin‐digested peptides were analysed by nanochromatography coupled to a high‐resolution mass spectrometer. Data‐dependent acquisition allowed protein identification that was processed by Paragon algorithm of Protein Pilot software. Results: Changes in the levels of epidermal differentiation proteins were apparent indicating poor epidermal differentiation and SC maturation (keratins, cornified envelope (CE) proteins) on photoexposed cheeks. Differences in protease–anti‐protease balance were observed for corneodesmolysis (favouring desquamation) and filaggrinolysis (favouring reduced filaggrin processing). 12R‐LOX, a CE maturation enzyme, was reduced in photodamaged skin but not transglutaminases. Changes in signal keratinocyte transduction pathway markers were demonstrated especially by reduced levels of downstream signalling markers such as calreticulin (unfolded protein response; UPR) and increased level of stratifin (target of rapamycin; mTOR). Evidence for impaired proteostasis was apparent by reduced levels of a key proteasomal subunit (subunit beta type‐6). Finally, key antioxidant proteins were upregulated except catalase. Conclusion: Clear examples of poor keratinocyte differentiation and associated metabolic and signalling pathways together with reduced SC maturation were identified in photodamaged facial SC. Corneocyte immaturity was evident with changes in CE proteins. Particularly, the reduction in 12R‐LOX is a novel finding in photodamaged skin and supports the lack of SC maturation. Moreover, filaggrinolysis was reduced, whereas corneodesmolysis was enhanced. From our results, we propose that there is a poor cross‐talk between the keratinocyte endoplasmic reticulum UPR, proteasome network and autophagy machinery that possibly leads to impaired keratinocyte proteostasis. Superimposed on these aberrations is an apparently enhanced mTOR pathway that also contributes to reduced SC formation and maturation. Our results clearly indicate a corneocyte scaffold disorder in photodamaged cheek SC. Abstract : A proteomic approach is described to investigate the impact of photodamage of facial stratum corneum in Caucasian subjects. We identified poor keratinocyte differentiation and associated metabolic and signalling pathways together with reduced SC maturation in photodamaged facial stratum corneum.